PROGNOSTIC COMPETENCE OF THE TEACHER: ESSENCE AND PLACE IN THE PROFESSIONAL STANDARD - Спіцин, Євгеній; Лещенко, Вікторія (Київський національний університет імені Тараса Шевченка, 2023)
Background. The article presents the analysis of prognostic competence of teacher. Authors support the point of view of Jerome B. Gardner, that a prognostic competence is an ability to understand the necessities of students and envisage the possible ways of their development, that include ability to observe students, analyse their behavior and give timely and corresponding support to them. Results. The prognostic competence of teacher not only envisages future results but also the ability to adapt oneself to the changes and create effective educational strategies. A prognostic competence can be examined as an ability of teacher to understand the necessities of students and envisage the possible ways of their development; it consists not only in the foresight of future results but also in ability to adapt oneself to the changes, to create effective educational strategies As the conducted analysis shows, a prognostic competence is important for teachers, as it allows to them to identify students that have difficulties in studies, and to render necessary support to them, to work out the individualized programs of studies, that deal with the necessities of students, plan lessons and activity, that are interesting for students, to create positive and supportive educational environment, where student can successfully study. Conclusions. The comparative analysis of structure of prognostic competence is conducted in the professional standards of teacher in Ukraine and Japan. In Japan in particular, the prognostic competence of teacher includes ability to take into account the necessities of certain generation, genetic transmission of experience, that it is related to that in the Japanese culture a large value is spared to traditions and domestic values. It is considered that experience that a person gets from the ancestors influences their personality and determines their way in life. Japanese teachers take into account influence of generation and genetic transmission of experience on development of the students. The prognostic competence of teacher in Japan is based on the general values of Japanese education, such as mutual respect, responsibility, harmony and independence. A teacher must take into account these values at planning, prognostication and realization of on-line tutorials.

Презентовано результати аналізу суті поняття "прогностична компетентність учителя". Під прогностичною компетентністю автори розуміють здатність учителя розуміти потреби учнів і передбачати можливі шляхи їхнього розвитку, що включає в себе здатність спостерігати за учнями, аналізувати їхню поведінку й надавати своєчасну та відповідну підтримку (Джером Б. Гарднер). Прогностична компетентність учителя передбачає не лише майбутні результати, але й здатність адаптуватися до змін і створювати ефективні освітні стратегії. Прогностичну компетентність можна розглядати як здатність вчителя розуміти потреби учнів і передбачати можливі шляхи їхнього розвитку; це полягає не лише в передбаченні майбутніх результатів, але і в здатності адаптуватися до змін, створювати ефективні освітні стратегії. Як показує проведений аналіз, прогностична компетентність є важливою для вчителів, оскільки вона дозволяє їм виявляти учнів, які мають складнощі в навчанні, і надавати їм необхідну підтримку, розробляти індивідуалізовані програми навчання, які враховують потреби учнів, планувати уроки й діяльність, які цікаві для учнів, створювати позитивне та сприятливе освітнє середовище, де учень може успішно навчатися. Проведено порівняльний аналіз структури прогностичної компетентності у професійних стандартах учителя в Україні та Японії. Зокрема, в Японії прогностична компетентність учителя передбачає здатність враховувати потреби певного покоління, генетичну передачу досвіду, що пов'язано з тим, що в японській культурі великого значення надають традиціям і домашнім цінностям. Вважається, що досвід, який людина отримує від предків, впливає на їхню особистість і визначає їхній шлях у житті. Прогностична компетентність вчителя в Японії ґрунтується на загальних цінностях японської освіти, таких як відповідальність, гармонія й незалежність.
ПРОГНОСТИЧНА КОМПЕТЕНТНІСТЬ УЧИТЕЛЯ: СУТЬ І МІСЦЕ У ПРОФЕСІЙНОМУ СТАНДАРТІ
Keywords: прогностична компетентність учителя; професійний стандарт учителя; система вищої освіти; підвищення кваліфікації вчителів; генетична передача досвіду; Японія.